(3QSGFd MeRI Hf Ydj GdOQRjs - (3GdaGQSqj GdMGcej GdOQRj, MeRI Hf Ydj Hf CMeO, J (B433 (3g`s
(3ChdgG (B:s
(3Ydi GdfUjQj dYfg Gdehdi aj cd chQ hOhQ JhcdJ Ydi ehdGfG GdHGQ GdYj SHMGfg CeG HYO CjPcQ CMOce Gdehdi HJCjjOg Cfg hQO Edi cJGH Cdag HYV GdfUjQjI GdcGaQjf (B...s
(3BNQgG (B:s
... (3heG gPG GdJYdb HMhdj hbhJj Hd HehGO bGFe Gdehdi Ld hYR Edi bGFe GdReGf hHYOg aEdi YHOgY GdHGFS GdabjQ hEf cGf ajg ef UhGH (B...(3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\278s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds